The origins and development of traditional medicine: an ideological issue - Eduardo L. Menéndez (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
Most analysts identify three main foundations of the development of traditional Mexican medicine between the 15th and 18th centuries (pre-Hispanic, Hispanic, and African), as well as a number of complementary sources incorporated over the course of the 18th and 19th centuries. However, a significant proportion of leading specialists consider pre-Hispanic medicine to be the primary basis of traditional medicine, downplaying Hispanic influence and disregarding African influence. Furthermore, they either ignore or give only cursory treatment to the role of biomedicine in the present-day medicalization of traditional medicine. Although this trend can be traced back to the 1930s and 1940s, it intensified from the 1970s onward and peaked around the time of the Fifth Centennial in 1992, transforming the question of the origins and development of traditional medicine into a largely ideological issue.